Prenatal subjective social status and birth weight - Dana K. Goplerud; Raquel G. Hernandez; Sara B. Johnson (Journal of Psychosomatic Obstetrics and Gynecology, 2022)
Purpose Subjective social status (SSS), perceived social standing relative to others, has been associated with health status, independent of objective socioeconomic status (SES). Few studies have examined the relationship of prenatal maternal SSS with birth outcomes. We evaluated the association of SSS in pregnancy with low birth weight (LBW) and high birth weight (HBW). Methods A total of 378 pregnant women rated their SSS from 1 (low) to 10 (high) compared to others in the United States (SSS-US) and compared to their community (SSS-Comm). Multivariable logistic regression was used to examine the relationship between SSS and odds of LBW or HBW. Results Higher SSS-US was associated with lower odds of HBW in unadjusted models (OR 0.76, 95% CI 0.60–0.96; p < 0.05); this relationship persisted after controlling for objective SES, health, and demographic factors (OR 0.73, 95% CI 0.53–0.99; p < 0.05). Neither SSS measure was associated with LBW. Conclusions Pregnant women who view themselves as having lower status than others in the US have greater odds of HBW, over and above the influence of factors known to be associated with birth weight. SSS, a brief and non-stigmatizing measure, might help identify women at elevated social risk for adverse birth outcomes.